Carbon markets proliferating despite difficulties, report notes. (11th June 2013) - Showstack, Randy
Abstract : Although some existing carbon markets are facing structural issues and economic difficulties in Europe have put a damper on the European Union emissions trading system, new carbon pricing initiatives are developing rapidly, and these initiatives could help slow down greenhouse gas emissions, according to a 29 May report from the World Bank.